Laryngeal palpation in thyroid surgery: practical recommendations for method integration into daily clinical practice according to comprehensive literature review and prospective cohort study results - Rybakovas, Andrius; Matulevičius, Andrius; Belogorceva, Viktorija; Beiša, Virgilijus; Strupas, Kęstutis (Lietuvos chirurgija, 2018)
[full article and abstract in Lithuanian; abstract in English]The incidence of thyroid surgery is steadily increasing. Recurrent laryngeal nerve injury is one of the most serious postoperative complications related to thyroid surgery, because it impairs patients’ quality of life, causes voice changes, or even respiratory dysfunction in case of bilateral nerve injury. To reduce the nerve injury rate various modern intraoperative techniques are used. One of the most effective strategies to avoid bilateral nerve injury is intraoperative neuromonitoring technique. This method effectively evaluates nerve function but is associated with increased costs. Laryngeal palpation may be a cheap alternative. However, it is not clear if this method is enough specific and sensitive. Therefore, to summarise method sensitivity, specificity, and clinical value we comprehensively reviewed current literature and presented the results of our prospective cohort study. According to various authors, laryngeal palpation method sensitivity and specificity for nerve injury detection varies between 33–100% and 92–100%, respectively. Our study showed similar results – laryngeal palpation is highly sensitive (100%) and specific (96.6%) method for intraoperative nerve function evaluation.After summarising current evidence, we suggested recommendation for method application in daily clinical practice: 1. Recurrent laryngeal nerve should be always identified during thyroid surgery. 2. Intraoperative neurostimulation is indicated in all cases when thyroidectomy is planned. If intraoperative neuromonitoring is not available, laryngeal palpation should be the method of choice. 3. In case of thyroidectomy intraoperative neurostimulation should be performed after first lobe mobilization to avoid bilateral nerve injury.
Keywords: thyroid surgery, laryngeal palpation, nerve injury, practical recommendations